Explainable Artificial Intelligence: Analysis of Methodologies and Applications - Pezzini, María Cecilia (2025)
Explainability is essential in healthcare, finance, and security, where black-box models can undermine trust and decisions. Recent advances in eXplainable Artificial Intelligence (XAI) across structured/tabular data, computer vision, and natural language processing are surveyed. Thirty articles (2022–2024) were selected through a structured search with explicit inclusion criteria, and emerging approaches are compared with established techniques such as LIME and SHAP, alongside rule-, logic-, and ontology-based methods. Methods are organized along key dimensions—post-hoc vs. ante-hoc, model-agnostic vs. model-specific, scope, problem type, input data, and output format—and their effectiveness and applicability are evaluated. The review highlights innovations including spatially explainable architectures (e.g., SAMCNet) and entropy-based logic explanations, and identifies persistent challenges in robustness, cross-domain generalization, and deployment. Overall, findings consolidate the evolving XAI landscape and indicate directions toward reproducible techniques that strengthen transparency, accountability, and user trust in AI systems.